Capacity Building in Context - Motsi, Alexio (My University, 2010)
The challenges (from an African perspective) • Lack of coherent approach • Limited understanding of the complex issues relating to digitization • Donor influence –many donors tend to enforce their own agendas • Lack of commitment at strategic levels • Legislative shortcomings • Lack of own resources • Improper prioritization
Keywords: ICADLA, conference, digital library, archive, Africa, capacity, national archives, records